(untitled) (Global Journal of Science Frontier Research, 2015)
In this paper a hierarchical structure for the management of airport ground handling activities is proposed. The main decision making processes in charge of the managerial units composing a proposed ground handling management organization are considered. The global objective is to turn available the ground handling resources so that arriving and departing flight are serviced with as little delay as possible. Two operational situations are considered: a normal one where small delays are coped with when arriving and departing traffic is globally on schedule, and a disrupted situation where arriving or departing traffic suffer very large delays.